Lady Chatterley: rewriting D. H. Lawrence’s novel on screen - Silva, Carlos Augusto Viana da (Acta Scientiarum. Language and Culture, 2017)
This paper analyses the rewriting of John Thomas and Lady Jane (1977), the second version of a representative modern narrative, Lady Chatterley’s Lover (1928), by D. H. Lawrence, and the corresponding film, Lady Chatterley (2006), by the French director Pascale Ferran. Based on theoretical principles of film adaptation as translation (Cattrysse, 2014), on the discussion of translation as a kind of rewriting (Lefevere, 1992), and on principles of intersemiotic translation (Plaza, 2001), the aspects of the process of the main characters’ construction and the reception of the film will be discussed, as well as its role in the representation of Lawrence’s search for a classical unity in his vision of man.